2020
DOI: 10.1002/ejhf.1984
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid, influence of sacubitril–valsartan, and cardiovascular outcomes in heart failure with preserved ejection fraction: PARAGON‐HF

Abstract: Aims This study aimed to determine the prognostic value of serum uric acid (SUA) on outcomes in heart failure (HF) with preserved ejection fraction (HFpEF), and whether sacubitril–valsartan reduces SUA and use of SUA‐related therapies. Methods and results We analysed 4795 participants from the Prospective Comparison of ARNI [angiotensin receptor–neprilysin inhibitor] with ARB [angiotensin‐receptor blockers] Global Outcomes in HF with Preserved Ejection Fraction (PARAGON‐HF) trial. We related baseline hyperuric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 32 publications
(55 reference statements)
1
29
0
3
Order By: Relevance
“…Indeed, animal models have shown that decreasing uric acid levels can prevent or reverse MS features [20], probably because hyperuricemia can induce endothelial dysfunction [21] and/or oxidative changes in adipocytes [22], which are typical stigmata of MS. Interestingly, all these features are increasingly described in HF with preserved ejection fraction (HFpEF), pointing to the existence of an inflammatory-metabolic phenotype [23]. A recent subanalysis from the PARAGON-HF trial demonstrated that hyperuricaemia was associated with an increased risk of adverse cardiovascular outcomes (CVM and HF hospitalisation) [24], suggesting that SUA may be a relevant therapeutic target also in HFpEF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, animal models have shown that decreasing uric acid levels can prevent or reverse MS features [20], probably because hyperuricemia can induce endothelial dysfunction [21] and/or oxidative changes in adipocytes [22], which are typical stigmata of MS. Interestingly, all these features are increasingly described in HF with preserved ejection fraction (HFpEF), pointing to the existence of an inflammatory-metabolic phenotype [23]. A recent subanalysis from the PARAGON-HF trial demonstrated that hyperuricaemia was associated with an increased risk of adverse cardiovascular outcomes (CVM and HF hospitalisation) [24], suggesting that SUA may be a relevant therapeutic target also in HFpEF.…”
Section: Discussionmentioning
confidence: 99%
“…Clearer identification of the patient phenotype in which SUA might have a greater impact on mortality could avoid further confusion in the future. Noteworthy, the risk of CVM may increase with SUA levels lower than those currently used in clinical practice to define the risk of gout [24]. This is of utmost importance, since there is an urgent need to develop and implement prevention and treatment strategies (e.g., lifestyle programs, diets, and pharmacotherapies) to reduce the CV burden.…”
Section: Metabolic Syndromementioning
confidence: 99%
“…The results of the PARAGON-HF trail are also of great importance for the redefinition of the heart failure classification, as suggested by the experts [1]. The last subanalyses of the trial also revealed the beneficial effect of ARNI on the serum uric acid level which was independently associated with increased risk for primary outcomes (rate ratio, 1.61; 95% CI, 1.37-1.9) [2], and the beneficial effect of the pulse pressure, a marker of arterial stiffness [3].…”
mentioning
confidence: 84%
“…Es gibt Hinweise dafür, dass diese Substanzen ebenfalls eine gewisse Harnsäuresenkung bewirken; man könnte vorsichtig optimistisch formulieren, dass dies eventuell für Patienten mit Herzinsuffizienz (gezeigt für Patienten mit Herzinsuffizienz und erhaltener Ejektionsfraktion, sog. HFpEF) und Gicht eine Option darstellt [31]. Bei Patienten mit einer Herzinsuffizienz muss aus symptomatischen (nicht aus prognostischen Gründen!)…”
Section: Therapie Kardiovaskulärer Risikopatienten Mit Hyperurikämieunclassified